Problem of Foreign Body in GI Tract - Yahya Daneshbod; Abdolrasoul Talei; Shahrzad Negahban; Hossein Soleimanpour; Azita Aledavoud; Neda Bagheri; Mahsa Khanlari; Khosrow Daneshbod (The Scientific World Journal)
Most foreign bodies pass through the gastrointestinal tract uneventful. We report of a case of inadvertently ingested foreign body, which by endoscopy simulated a polyp and on biopsy reported as cancer, so the patient underwent an unnecessary major operation. This report emphasizes the importance of resemblance of foreign bodies with gastrointestinal neoplasm, and endoscopists, surgeons and pathologists should consider this entity in their daily practice.